Conceptions of teaching: an illustrated review. (18th January 2017) - Ross, Michael
Summary: Background: Asking teachers what the term 'teaching' means to them can be a useful first activity in a faculty development session, as it typically leads to an engaging and enlightening discussion for participants and facilitators. Mapping their responses to 'conceptions of teaching' (sets of assumptions, knowledge and beliefs about teaching) in the literature seems particularly helpful in illuminating the inconsistencies, gaps and additional ways of thinking about teaching that participants may wish to consider. Literature review: At least 25 conceptions of teaching can be identified in the literature. Each of these are briefly described and illustrated in this article, along with detailed examples and suggestions of how conceptions of teaching can be explored in faculty development. There is evidence that a teacher's conceptions of teaching affect the way that they approach their teaching, which in turn can affect learner learning. There is also some evidence that helping teachers examine and develop their conceptions of teaching may be more effective and have more impact on learner learning than other forms of faculty development. Take‐home messages: Different conceptions of teaching seem to be more or less appropriate in different teaching situations and contexts. It is likely that the more ways in which teachers can conceptualise and reflect on what they are doing, and why, the more adaptable, responsive and effective their teaching will be. Teachers have much to gain from learning more about themselves, their values and assumptions, and how these can influence their practice. This article offers a practical approach aimed at helping them to achieve this. A teacher's conceptions of teaching affect the way that they approach their teaching